MENINGKATKAN KEMAMPUAN BERPIKIR ILMIAH PESERTA DIDIK KELAS VIII MELALUI PEMBELAJARAN BERBASIS MASALAH MATERI ZAT ADITIF - Andarista, Shefi; Rosdiana, Laily (PENSA E-JURNAL: PENDIDIKAN SAINS, 2023)
This research aimed to describe the improvement of students' scientific thinking skills on additive material using problem-based learning model implemented in one of public Junior High Schools in Surabaya. This research design used one-group pretest-posttest. This research involved 36 students of class VIII. This research's data collection methods included observation, tests, and questionnaires. The results showed that the implementation of problem-based learning got the average result from two meetings at 94.5% (very good). The average normalized gain for all students in the medium category. The average normalized gain of students in each sub-indicator of scientific thinking ability, namely: inquiry and analysis, increased in the high category, while inference and argumentation increased in the medium category. The students' responses to problem-based learning got very good results. Therefore, it can be concluded that problem-based learning can improve scientific thinking skills on additive material.